Content validation of the Nutritional Attention Assessment Instrument in Primary Health Care - PACITO-ALMEIDA, Ana Beatriz; Barbosa Neres SANTANA, Angélica; Oikawa ZANGIROLANI, Lia Thieme; Tavares de MEDEIROS, Maria Angélica (Revista de Nutrição, 2023)
Objective Construct and validate the content of an instrument to evaluate the organization of nutritional care in Primary Health Care in Brazil. Methods This is a cross-sectional and validation study. The construction of the Nutritional Attention Assessment Instrument was based on literature review and review of official documents. The instrument was submitted to content validation using the Delphi technique in two rounds. Results The validation panel consisted of 29 specialists from the five Brazilian Macroregions: 13 higher education teachers/investigators, seven food and nutrition managers, four Primary Health Care professionals and five professionals knowledgeable of the subject, most of them (89.7%) working in the public service with experience of over six years. The validated instrument contains 68 questions and 10 indicators: (1) Nutritionist performance; (2) Support to the Nutritional Attention actions: infrastructure and permanent education; (3) Intersectoriality; (4) Social Control; (5) Food and Nutrition Surveillance; (6) Individual Nutritional Attention; (7) Nutritional Attention for Groups; (8) Nutritional Attention focused on prenatal care; (9) Nutritional Attention focused on postpartum/ breastfeeding and (10) Nutritional Attention focused on child health. Conclusion The proposed instrument is an advance which enables the establishment of evaluation processes for Nutritional Attention. It is expected that this instrument be widely used to evaluate the Nutritional Attention given in the municipalities, states and at the federal level. The results obtained with future applications may contribute to support management qualification of food and nutrition policies.